Improved Data Visualization Capability Using Microsoft Excel for Teachers - Faula Arina; Mukhtar Mukhtar; Rafli Priyantama Ramadhan Bagaskara; Syukron Faiz; Muhammad Fabian Reinhard Delano (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Abstract. The digital era demands that all institutional infrastructure components must be able to adapt so that the management of their activities is effective and efficient. However, the lack of knowledge and skills of teachers at the Fajrul Karim Islamic Boarding School in operating Excel is a major obstacle. Data visualization is one method of conveying information studied in statistics. The Excel training provided aims to provide an understanding regarding the application of statistical methods with Excel and its visualization so that teachers at the Fajrul Karim Serang Banten Islamic boarding school can better understand student grades. The material covered includes data organization, descriptive statistics, pivots, and an introduction to charts. As a result of the training provided, training participants were able to visualize student value data. The program results obtained are increased knowledge and skills in analyzing and visualizing data based on statistics and Excel.